(untitled) (Research, Society and Development, 2021)
The virtual world is a reality for teenagers around the world. Consequence of this, it is a medium in which it can be a facilitator of symptoms of eating disorders. Eating disorders occur due to psychological and behavioral changes and affect health, especially in young individuals. The objective of the systematic review is to understand how these mass media interfere with eating disorders. 27 articles were found in the PubMed, LILACS and SciELo databases in the last 10 years after inclusion and exclusion criteria. The results obtained were the prevalence of eating disorders in female adolescents, secondly, the persuasion and subversion of mass media over an audience without a power of criticism. Also, reflexes of these disturbances in body dissatisfaction and low self-esteem arising from utopian bodies supported by society and aired on the internet. The dynamics found are the socialization of young people in the context of creating perfect bodies and ideal models, especially among adolescent women, who are under pressure from patriarchy. As a result, psychological suffering expands to body dissatisfaction and, finally, communication and marketing strategies actively act on this vulnerability of this social group. Thus, it was analyzed that social networks increase the spread of eating disorders with this, it is necessary to regulate the use of social networks and media education so that criticality is stimulated in young people together with psychological support.